HEMATOLOGICAL DATA ON THE FISHES OF THE GENUS MUGIL LINNAEUS - Pitombeira, Maria da Silva; Gomes, Francisca Vânia Barreto; Martins, José Murilo (Arquivos de Ciências do Mar, 2018)
The present paper is a contribution to the knowledge of the hematology of mullets of the genus Mugil Linnaeus from the northeastern Brazil. Only the species Mugil curema Cuvier & Valenciennes and Mugil incilis Hancock were considered.